A Bispecific Antibody Based on Pertuzumab Fab Has Potent Antitumor Activity. Issue 1 (January 2018) - Deng, Wentong; Liu, Jiayu; Pan, Haitao; Li, Li; Zhou, Changhua; Wang, Xiaojuan; Shu, Rui; Dong, Bin; Cao, Donglin; Li, Qing; Wang, Zhong
Abstract : Human epidermal growth factor receptor 2 (HER2) is frequently overexpressed and activated in metastatic breast cancers. Monoclonal antibodies targeting Her2, such as trastuzumab and pertuzumab, have become important targeted therapies for patients with HER2-positive breast cancer. Both trastuzumab and pertuzumab can reduce Her2 positive tumor burden by inhibiting Her2 signaling and inducing ADCC activities (antibody dependent cell-mediated cytotoxicity). In this study, we have generated a bispecific antibody, Her2(Per)-S-Fab, by linking the pertuzumab Fab to an anti-CD16 single domain antibody. The Her2(Per)-S-Fab can be expressed and purified efficiently from Escherichia coli . In vitro and in vivo experiments showed Her2(Per)-S-Fab had potent cytotoxicity against Her2-positive tumor cells. Thus, Her2(Per)-S-Fab may provide an alternative to treat Her2-positive cancer patients.